Empowering Women through Maternal Health Education: Impacts on Decision-Making and Health Outcomes - Ummi Nazeera; Rifka Ramadhani (Generasi Sains Indonesia, 2025)
The effects of maternal health education on women's decision making autonomy and maternal health outcomes in Indonesia are explored. Data were obtained from 305 women of reproductive age by structured questionnaires in a quantitative cross sectional design and analyzed by descriptive statistics, regression analysis and mediation analysis. The results show that maternal health education has a significant effect on increasing women's autonomy in decision making regarding health services and utilization of antenatal, facility-based delivery and postnatal health services. The study also indicates that the relationship between maternal health education and maternal healthcare utilisation is partially mediated by women's decision making autonomy. The novelty of the research is the incorporation of an education intervention and empowerment approach in analyzing maternal health care. The results suggest that maternal health programs need to go beyond informing to include strategies that empower women, thereby enhancing their agency and access to healthcare. This study is a step towards more inclusive and sustainable policies for maternal health care in the context of a developing country.